The non-invasive biopsy: will urinary proteomics make the renal tissue biopsy redundant? - Bramham, K.; Mistry, H.D.; Poston, L.; Chappell, L.C.; Thompson, A.J. (Oxford University Press, 2009)
Proteomics is a rapidly advancing technique which gives a functional insight into gene expression in living organisms. Urine is an ideal medium for study as it is readily available, easily obtained and less complex than other bodily fluids. Considerable progress has been made over the last 5 years in the study of urinary proteomics as a diagnostic tool for renal disease. The advantages of this technique over the traditional renal biopsy include accessibility, safety, the possibility of serial sampling, and the potential for non-invasive prognostic and diagnostic monitoring of disease and an individual’s response to treatment. Urinary proteomics is now moving from a discovery phase in small studies to a validation phase in much larger numbers of patients with renal disease. Whilst there are still some limitations in methodology, which are assessed in this review, the possibility of urinary proteomics replacing the invasive tissue biopsy for diagnosis of renal disease is becoming increasingly realistic.